Enhanced glucose metabolism in Tet-deficient mouse embryonic stem cells - Yang, Yuhan; Cavalier, Maryn; Suris, Ashley; Chen, Kevin; An, Claire; Fan, Jingyuan; Rivera, Logan; Fang, Shaohai; Guo, Lei; Zhou, Yubin; Huang, Yun (Frontiers in Epigenetics and Epigenomics, 2024)
Interactions between epigenetics and metabolites play critical roles in regulating the pluripotency and differentiation of embryonic stem cells. Proper glucose metabolism and DNA methylation are essential for orchestrating accurate lineage specification and the normal functions of embryonic stem cells. However, the impact of Ten-eleven Translocation (TET)-mediated DNA methylation modifications on the metabolism of mouse embryonic stem cells (mESCs) remains less well defined. In this study, we investigated the consequences of Tet triple knockout (Tet-TKO) in mESCs and observed notable alterations in glucose metabolism. These changes were marked by enhanced glucose uptake and glycolysis, likely owing to the upregulation of genes critical for glucose metabolism. Furthermore, Tet-TKO mESCs exhibited defects in glucose-dependent differentiation, suggesting that cells with epigenetic defects might display metabolic vulnerability when exposed to external nutritional cues. Collectively, our findings establish the pivotal role of the TET family of dioxygenases in maintaining proper glucose metabolism and safeguarding stem cell lineage specification, thus enhancing our understanding of the intricate interplay between epigenetic modifications and cellular metabolism in stem cells.